Effect Of Bar Sealing Parameters On OPP/MCPP Heat Seal Strength - Hassan, Azman; Cheng, See Yuan (eXPRESS, 2007)
The effect of bar sealing parameters on the heat seal strength of oriented polypropylene (OPP)/metallic cast polypropylene (MCPP) laminate film was investigated. Based on the results obtained from the parametric study, a bar sealing process window was developed. All points drop within the process window are combinations of platen temperature and dwell time that produce acceptable heat seal. Optimum combinations are indicated by the lower border of the window. The plateau initiation temperature, Tpi of OPP/MCPP laminate film used in the present study occurred before the final melting temperature, Tmf of the sealant material. The highest achievable heat seal strength was at the plateau region, and the corresponding failure modes were delaminating, tearing or combine failure modes (delaminating and tearing). Minimum pressure level of 1.25 bars is necessary to bring the laminate interface into intimate contact in order to effect sealing.